2014
DOI: 10.1371/journal.pone.0084741
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Regional Species Pool, Ecological Species Traits and Local Habitat Conditions for the Colonization of Restored River Reaches by Fish

Abstract: It is commonly assumed that the colonization of restored river reaches by fish depends on the regional species pools; however, quantifications of the relationship between the composition of the regional species pool and restoration outcome are lacking. We analyzed data from 18 German river restoration projects and adjacent river reaches constituting the regional species pools of the restored reaches. We found that the ability of statistical models to describe the fish assemblages established in the restored re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 51 publications
7
60
0
Order By: Relevance
“…This is consistent with the higher mean effect on macroinvertebrate abundance ( r = 0.21) compared to richness ( r = 0.08) reported in Miller et al (2010) and recent empirical and modelling studies which showed that the species pool and source populations for colonization are often sparse and limit the effect of restoration on species richness (Radinger and Wolter, 2015;Stoll et al, 2014;Tonkin et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with the higher mean effect on macroinvertebrate abundance ( r = 0.21) compared to richness ( r = 0.08) reported in Miller et al (2010) and recent empirical and modelling studies which showed that the species pool and source populations for colonization are often sparse and limit the effect of restoration on species richness (Radinger and Wolter, 2015;Stoll et al, 2014;Tonkin et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…As recently found with fish (Stoll et al, 2013(Stoll et al, , 2014, and in line with our final hypothesis, the results of the BRT model show that it is not just the presence within the surrounding area but the rate of occurrence of taxa that affects colonisation chances, with density of occurrence in the regional pool being the most important dri-ver of site presence. Taxon identity and restoration site location were overwhelmingly influential in the BRT models when they were included, but cross-validation highlighted they were not strong predictors of general patterns.…”
Section: Discussionsupporting
confidence: 88%
“…Differentiating between DL, ME and SS is of fundamental importance, not only for enhancing our basic understanding, but for practical reasons, including biomonitoring and restoration (Heino et al ). Recent work clearly demonstrated that the response of stream communities to restoration was highly dependent on the availability of colonists in the surrounding regional pool, particularly the distance to the nearest colonist and species ubiquity (Stoll et al , Tonkin et al ). In their studies, these factors were the overriding drivers of restoration response.…”
Section: Discussionmentioning
confidence: 99%